Implementation of the Motif Mapping Technique in Garment Pattern–Based Ecoprint Production - Kurnia Rizkya Sang Saka Maharani; Rina Rachmawati (Jurnal Penelitian Pendidikan, 2026)
This study focuses on the development of a motif mapping and arrangement technique for ecoprint based on garment pattern pieces. Ecoprint motifs often appear fragmented, uneven, and visually unfocused because leaves are typically arranged on whole fabric without considering the garment pattern structure. The innovation of this research is the application of a pre-mapping process, in which garment patterns are drawn on pre-mordanted fabric prior to leaf arrangement, ensuring that motif placement follows pattern boundaries and maintains motif continuity.This study applies a modified 4D Research and Development model, supported by observation, experimentation, documentation, and expert evaluation. The findings indicate that the motif mapping technique is capable of producing a more structured motif composition that is well integrated with garment patterns, thereby enhancing both aesthetic value and visual unity in ecoprint products. The motifs no longer appear random or fragmented; instead, they form a cohesive visual flow aligned with the garment design. In addition, this technique provides greater control over motif placement, ensuring continuity across different sections of the garment. Based on expert evaluation, the resulting product falls within the good to very good category in terms of composition, neatness, and motif–pattern compatibility. Therefore, the Motif Mapping Technique can be considered an innovative alternative in pattern-based ecoprint design, offering a more structured approach and improved aesthetic outcomes.